Plant Invasions and Global Climate Change - Tripathi, Sachchidanand; Bhadouria, Rahul; Srivastava, Priyanka; Singh, Rishikesh; Batish, Daizy R. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited book provides an ensemble of contemporary research related to the challenges, impacts and precautionary measures for tackling plant invasions in the context of changing climate in different regions of the world. In current scenario, plant invasions are expansive and significant component of anthropogenic global climate change. Temperature variations may compromise the adaptability of native species, thereby stressing them and decreasing the resistance potential of natural communities to invasion. Invasive alien species under the current scenario have been suggested as a major threat to biodiversity. It is also predicted that increasing disturbances or extreme events such as fires, floods, cyclones, storms, heat-waves, droughts, etc. will be direct consequences of changing climate supporting the invasive alien species. A comprehensive understanding of the interaction between species invasion and climate change will be supplemental in forecasting future shifts in biodiversity. Further, different predictive models indicate a plausible increase in the abundance and impact of invasive alien species which may have direct implications for future research and target-oriented policy and decision making. However, these predictions become more complicated considering the complexity of interactions between the impacts of changing climate with other components of global change (changes in land use, nitrogen deposition, etc.) which are affecting the distribution of native plant species, ecosystem dynamics as well as non-native/invasive species. This book will be suitable for students (undergraduate and postgraduates) of agriculture, forestry, ecology, soil science, and environmental sciences; teachers, researchers, and climate change scientists in academic and research institutions. It will also be applicable to environmental management agencies, government agencies and policy makers. .
Ch 1. Plant invasion and climate change: a global overview -- Ch 2. Impacts of plant invasions on ecosystem functionality: a perspective for ecosystem health and ecosystem services -- Ch 3. Menace of Plant Invasion: A View from Ecological Lens -- Ch 4. Role of extreme climate events in amplification of plant invasion -- Ch 5. Plant Invasion as Gleaned from Parasara's Vrkshayurveda -- Ch 6. Water, wind, and fire: extreme climate events enhance the spread of invasive plants in sensitive North American ecosystems -- Ch 7. Understanding eco-geographical relationship in invaded ranges by Acacia longifolia (Andrews) Willd. - An intercontinental case study on Acacia invasions -- Ch 8. Invasive plants in India: their adaptability, socio-ecological impacts, and response to changing climate -- Ch 9. Plant invasion in an aquatic ecosystem: A new frontier under climate change -- Ch 10. Plant invasion and soil processes: A mechanistic understanding -- Ch 11. Plant invasion dynamics in mountain ecosystems under changing climate scenario -- Ch 12. The role of epigenetics on plant invasions under climate change scenario -- Ch 13. Comparative assessment of Machine Learning Algorithms for habitat suitability of Tribulus terrestris (Linn): An economically important weed -- Ch 14. Strategies of plant invasion and management for the conservation and restoration of degraded poor agricultural lands -- Ch 15. Plant Invasion and Climate Change: An Overview on History, Impacts and Management Practices -- Ch 16. Biochar: a tool for combatting both invasive species and climate change -- Ch 17. An action plan to prevent and manage alien plant invasions in India.
Keywords: Botany; Plant ecology; Plant diseases; Plant Science; Plant Ecology; Plant Pathology